Talent Mapping: Menuju Jenjang Pendidikan yang Lebih Tinggi - Silvia, Ani; Adji, Fanina (Faculty of Economics and Business, University of Muhammadiyah Prof. DR. HAMKA, 2018)
As an educational institution in the middle level, Muhammadiyah 4 Senior High School has a significant role in mapping the superior potential of its students. At this level, students are expected to know their interests and talents in a particular field. Once interest and talent are identified, students can focus on choosing study programs that are appropriate to their respective interests and talents. Having a clear target will make students more motivated to optimize their academic value in preparation for the target program. For this reason, schools need to map superior potential for their students to achieve the vision and mission set by the school. Through interest and talent tests and seminars organized by the FEB-UHAMKA lecturer team in the framework of community service through community partnership programs, it is expected to help the school to do this mapping. Superior potential mapping is done to prepare excellent human resources because they have expertise in their specific fields. Without mapping, schools are expenses or costs that will just disappear. Conversely, by doing talent mapping, schools will be an investment that provides benefits both for the individual itself and for the wider environment. Keywords: talent mapping, interest, talent, study program